ESG Disclosures, Assurance Report, and Companies’ Attractiveness: Saudi Capital Market - Mohammed, Hanin Ahmed; Shah, Sabarina Mohammed; Yusri, Yusniyati; Ngalim, Manisah bt (Advances in Social Sciences Research Journal, 2024)
Environmental, Social, and Governance (ESG) practices are increasingly adopted by companies worldwide to align with sustainable development goals (SDGs), with Saudi Arabia emerging as a significant example of this global shift. This study investigates the role of ESG disclosures in enhancing corporate attractiveness and overall performance, particularly within the context of Saudi Arabia’s evolving economy. Grounded in legitimacy theory, the research explores how non-audit services, specifically ESG assurance reports, can validate a company’s sustainability claims and mitigate risks associated with greenwashing. Through a comprehensive literature review and analysis of key variables, this paper assesses the potential impact of mandatory ESG assurance requirements on corporate transparency and accountability. The findings offer insights valuable to practitioners, policymakers, and scholars interested in promoting socially responsible business practices.